Evaluating Pull-Out Behavior of Timber Connections: A Comparison of Dowelled Joints and Axially Loaded Screws - Haksung Lee; Man-Kwon Choi; Bo-Seong Seo; Young-Seok Cho; Byung-Joo Kim (Buildings)
This study examines the pull-out behavior of timber elements connected using dowelled joints (type 1) and axially loaded screws (type 2), focusing on numerical predictions and experimental validation under various conditions. Different screw diameters, configurations, material properties, and corrosion resistance are examined. Pull-out tests demonstrated that type 2 connections, particularly using 10 mm and 14 mm screws, outperformed traditional dowelled joints in terms of load capacity. Numerical analysis based on Eurocode 5 showed close alignment with experimental results, particularly for screws with actual thread diameters of 5.2 mm and 6.2 mm, with minor deviations attributed to material variability. The finite volume method (FVM), implemented using the Geodict ElastoDict software, provided additional insights into the mechanical behavior of the connections. Corrosion resistance tests confirmed the long-term durability of fiber-reinforced polymer (FRP) components in saline environments, with negligible material degradation after 28 days of exposure. The 10-90-6 screw configuration was identified as the most efficient, balancing load capacity, displacement, and material cost. These findings highlight the effectiveness of both Eurocode 5 and FVM-based approaches for predicting screw behavior and emphasize the importance of accounting for material heterogeneity in timber connection design.